PENGARUH PERLAKUAN AMONIASI DAN FERMENTASI KULIT SINGKONG TERHADAP NILAI KECERNAAN PROTEIN KASAR DAN SERAT KASAR PADA DOMBA EKOR TIPIS JANTAN - Ilhamsah Ilhamsah; Muhtarudin Muhtarudin; Agung Kusuma Wijaya; Liman Liman (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to determine the effect of ammoniation and fermentation of cassava peel on the digestibility of crude protein and crude fiber and the best effect of ammoniation or fermentation on the digestibility of crude protein and crude fiber in thin-tail sheep. This research was conducted in April-August 2019 in the sheepfold of Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research used 9 male thin-tail sheep, feedstuff, and sheepfold with 9 pens and feed bunk. This study used a Completely Randomized Design (CRD) consisted of 3 replications and 3 treatments. The treatments given were R0 (basal ration + 15% cassava peel), R1 (basal ration + 15% fermented cassava peel) and R2 (basal ration + 15% ammoniated cassava peel). Data were analyzed with analysis of variance and continued with Least Significant Difference Test (LSD) at 5% and or 1% significant level. The results showed that the effect of ammoniation and fermentation treatment of cassava peel had no significant effect (P> 0.05) on crude protein digestibility and crude fiber digestibility. Keywords: Thin-tail sheep, Crude protein, Crude fiber, Ammoniated and fermented cassava peel, digestibility